Inibição beta-adrenérgica reduz a incidência e o crescimento do carcinoma espinocelular de boca induzido por 4NQO em ratos - Cecilio, Heitor Pinhata [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Recent studies have shown that beta-adrenergic receptors activation can influence cancer progression. However, there are no studies which have investigated the role of beta-adrenergic receptors on the oral carcinogenesis in preclinical models. The main goal of this study was to evaluate the effects of beta-adrenergic inhibition on the chemically induced oral carcinogenesis in rats. Sixty-four male Wistar rats were divided into two groups: Propranolol group: The animals were treated with a beta-adrenergic antagonist propranolol (10mg/kg diluted in PBS via subcutaneous); Control group (Sham): The animals were treated subcutaneously with vehicle alone (PBS). Both groups were submitted to an oral carcinogenesis model by the treatment with carcinogen 4-nitroquinoline-1-oxide (4NQO) diluted in drinking water for 16 weeks. After 16 weeks of carcinogenic induction, the animals were euthanized and the tongue was removed. Histopathological examination was performed to evaluate the presence and extention of tongue squamous cell carcinomas (SCCs). Specific statistical tests were performed to evaluate the differences in the cancer incidence and progression between the two experimental groups. Our results showed that rats in the Propranolol Group had a lower tumor incidence and thickness when compared to the control group. However, our tests did not show significant diferences between tumor volume and degree of malignacy when the groups were compared. Knowing that, the beta-adrenergic signaling blockade may reduce cancer incidence and thickness on a preclinical model

Estudos têm mostrado a participação dos receptores beta-adrenérgicos na progressão de diversos tipos de câncer. Entretanto, inexistem estudos que avaliaram a participação destes receptores no processo de carcinogênese bucal em modelos pré-clínicos. O objetivo do presente estudo foi avaliar os efeitos da inibição beta-adrenérgica sobre a incidência e progressão do carcinoma espinocelular (CEC) de boca induzido pelo carcinógeno químico 4-nitroquinolina-1-oxido (4NQO) em ratos. Foram utilizados 64 ratos machos Wistar divididos em dois grupos. Grupo Propranolol: 32 animais tratados com o antagonista beta-adrenérgico propranolol (10 mg/kg diluído em PBS, via subcutânea). Grupo Sham (controle): 32 animais tratados com o veículo PBS (via subcutânea). Os animais de ambos os grupos foram submetidos por 16 semanas ao modelo de carcinogênese bucal induzida por 4NQO quando então foram eutanasiados para avaliação histopatológica da ocorrência de CEC em dorso de língua. Os resultados mostraram que os ratos tratados com Propranolol tiveram menor incidência e espessura de CEC de boca quimicamente induzido do que os animais do grupo controle. Entretanto, não observamos diferenças significativas entre os dois grupos quanto às análises do volume tumoral e do grau de malignidade das lesões tumorais. A inibição beta-adrenérgica pode reduzir a incidência do câncer de boca quimicamente induzido em modelos pré-clínicos
Keywords: Cancer; Neoplasias bucais; Carcinogênese; Receptores adrenérgicos; Propranolol; Mouth neoplasms